Learning in the Thick of It - Darling, Marilyn; Parry, Charles; Moore, Joseph (Harvard Business Review, 2005)
After-action reviews identify past mistakes but rarely enhance future performance. Companies wanting to fully exploit this tool should look to its master: the U.S. Army’s standing enemy brigade, where soldiers learn and improve even in the midst of battle.
Keywords: Aerospace sector; Corporate governance; Decision making and problem solving; Defense industry; Defense sector; Fabrication and manufacturing; Meeting management; Military; North America; Organizational culture; Presentation skills; Project management; Psychology; Telecom

Team of Teams: New Rules of Engagement for a Complex World - McChrystal, General Stanley; Silverman, David; Collins, Tantum; Fussell, Chris (Portfolio Penguin, 2015)
As commander of Joint Special Operations Command (JSOC), General Stanley McChrystal discarded a century of management wisdom and pivoted from a pursuit of mechanical efficiency to organic adaptability. In this book, he shows how any organization can make the same transition to act like a team of teams - where small groups combine the freedom to experiment with a relentless drive to share their experience.Drawing on a wealth of evidence from his military career and sources as diverse as hospital emergency rooms and NASA's space program, McChrystal frames the existential challenge facing today's organizations, and presents a compelling, effective solution.